Twenty Years of Business Information Literacy Research: A Scoping Review - Houlihan, Meggan A.; Click, Amanda B.; Walker Wiley, Claire (Evidence Based Library and Information Practice)

(untitled) (University of Alberta Library, 2020)
Objective – This study analyzes and synthesizes the business information literacy (BIL) literature, with a focus on trends in publication type, study design, research topic, and recommendations for practice.Methods – The scoping review method was used to build a dataset of 135 journal articles and conference papers. The following databases were searched for relevant literature published between 2000 and 2019: Library and Information Science Source, Science Direct, ProQuest Central, Project Muse, and the Ticker journal site. Included items were published in peer reviewed journals or conference proceedings and focused on academic libraries. Items about public or school libraries were excluded, as were items published in trade publications. A cited reference search was conducted for each publication in the review dataset. Results – Surveys were, by far, the most common research method in the BIL literature. Themes related to collaboration were prevalent, and a large number of publications had multiple authors or were about collaborative efforts to teach BIL. Many of the recommendations for practice from the literature were related to collaboration as well; recommendations related to teaching methods and strategies were also common. Adoption of the Framework for Information Literacy for Higher Education in BIL appears slow, and the citations have decreased steadily since 2016. The majority of the most impactful BIL articles, as measured by citation counts, presented original research.  Conclusions – This study synthesizes two decades of literature and contributes to the evidence based library and information science literature. The findings of this scoping review illustrate the importance of collaboration, interest in teaching methods and strategies, appreciation for practical application literature, and hesitation about the Framework.